2014
DOI: 10.1080/09593330.2014.989279
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable landfill leachate treatment using refuse and pine bark as a carbon source for bio-denitrification

Abstract: Raw and 10-week composted commercial garden refuse (CGR) materials and pine bark (PB) mulch were evaluated for their potential use as alternative and sustainable sources of carbon for landfill leachate bio-denitrification. Dynamic batch tests using synthetic nitrate solutions of 100, 500 and 2000 mg NO3 L(-1) were used to investigate the substrate performance at increasing nitrate concentrations under optimal conditions. Further to this, sequential batch tests using genuine nitrified landfill leachate with a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Administration of rRH‐HA enhanced the stability of aerobic system compared with RH and AS system determined by microbial concentration (Figure 2c). Sustainable sources of carbon for landfill leachate bio‐denitrification provide an easily implementable framework and contribute to high efficiency of pollutant removal for large‐scale applications (Frank et al, 2015). Our data showed that rRH‐HA system decreased the requirement of carbon source compared with RH and AS system in the treatment of landfill leachate (Figure 2d).…”
Section: Resultsmentioning
confidence: 99%
“…Administration of rRH‐HA enhanced the stability of aerobic system compared with RH and AS system determined by microbial concentration (Figure 2c). Sustainable sources of carbon for landfill leachate bio‐denitrification provide an easily implementable framework and contribute to high efficiency of pollutant removal for large‐scale applications (Frank et al, 2015). Our data showed that rRH‐HA system decreased the requirement of carbon source compared with RH and AS system in the treatment of landfill leachate (Figure 2d).…”
Section: Resultsmentioning
confidence: 99%
“…Excess nutrients in water can cause issues, such as eutrophication. Many studies have found that woodchips remove nutrients from water, including nitrate, sulphate, ammonia, ammonium, nitrite, orthophorphorus, and particulate phosphorus [2,3,5,6,9,[11][12][13][14][15][16][17]. Nutrients vary in their chemical properties, so their removal processes vary as well.…”
Section: Nutrientsmentioning
confidence: 99%